Determination of reactivation rate and risk factors for Hepatitis B virus reactivation in low-positive cases: A retrospective cohort study. Issue 10 (October 2021) - Yonezawa, Hitoshi; Tanaka, Shingo; Furuya, Momoko; Yamada, Koji; Asanuma, Koichi; Fujiya, Yoshihiro; Miyanishi, Koji; Takahashi, Satoshi; Kato, Junji
Abstract: Introduction: In quantitative assays for hepatitis B virus (HBV) DNA, although the amplification reaction signal is detected for low-positive cases, quantification remains challenging. HBV reactivation has been reported in many studies, but only a few have focused on HBV low-positive cases. This study aimed to determine the reactivation rate and risk factors for HBV reactivation in low-positive cases. Methods: In this retrospective cohort study, we analyzed 7498 patients who had their HBV DNA measured at Sapporo Medical University Hospital between April 2008 and November 2020. Patient selection criteria were defined as follows: hepatitis B surface antigen was negative; HBV DNA was detectable but not quantifiable at least once. HBV DNA was monitored according to the guidelines for HBV reactivation. Results: In total, 49, 086 HBV DNA quantitative tests were performed. HBV DNA levels of 2578 tests were detectable but not quantifiable. Eighty patients met the criteria in this study. The median observation period was 497 days, and the 2-year reactivation rate was 15%. Ten patients had low HBV DNA positivity at baseline. Malignant lymphoma was observed in 15 patients; chemotherapy was used to treat other solid tumors in 35 patients, and immunosuppressive therapy was used in 30 patients. Multivariate analysis revealed that HBV DNA detected below the quantification level at baseline was an independent risk factor for HBV reactivation (adjusted hazard ratio 5.82; P  = 0.010). Conclusions: Patients with low HBV DNA positivity, especially at baseline, are at high risk for HBV reactivation and therefore require closer monitoring.